Determination of δ-opioid receptor molecules mobility in living cells plasma membrane by novel method of FRAP analysis - Janáček, Jiří; Brejchová, Jana; Svoboda, Petr (Biochimica et biophysica acta. Biomembranes, 2019)
Fluorescence recovery after photobleaching (FRAP) is the preferred method for analyzing the lateral mobility of fluorescently-tagged proteins in the plasma membranes (PMs) of live cells. FRAP experiments are described as being easy to perform; however, the analysis of the acquired data can be difficult. The evaluation procedure must be properly combined with the imaging setup of the confocal microscope to provide unbiased results. With the aim of increasing the accuracy of determining the diffusion coefficient (D) and mobile fraction (Mf) of PM proteins, we developed a novel method for FRAP analysis in the equatorial plane of the cell. This method is based on the calculation of photobleaching characteristics, derived from the light intensity profile and optical parameters of the confocal microscope, and on the model of fluorescent molecule diffusion in PM regions outside of the focal plane. Furthermore, cell movement artifacts in the FRAP data are ameliorated by using a region of interest, which is not fixed but instead moves adaptively in coordination with the movement of cells. When this method was used to determine the mobility of the δ-opioid receptor-eYFP in HEK293 cells, a highly significant decrease in receptor mobility was detected in cholesterol-depleted cells. This decrease was fully reversible by the replenishment of cholesterol levels. Our results demonstrate the crucial role played by cholesterol in the dynamic organization of δ-opioid receptors in the PM under in vivo conditions. Our method may be applied for the determination of the D and Mf values of other PM proteins.
Keywords: cholesterol; Cholesterol replenishment; FRAP; Adaptive ROI approach; HEK293 Cells; lidé; receptory opiátové delta; Receptors, Opioid, delta; HEK293 buňky; Cholesterol; Artifacts; Plasma membrane; Fluorescence Recovery After Photobleaching; Cholesterol depletion; buněčná membrána; δ-Opioid receptor-eYFP mobility; artefakty; Cell Membrane; Humans